Bone response to porous alumina implants coated with bioactive materials, observed using different characterization techniques - Camilo, Claudia C.; Silveira, Celey A. E.; Faeda, Rafael S. [UNESP]; Almeida Rollo, Joao M. D. de; Purquerio, Benedito de Moraes; Fortulan, Carlos Alberto (Wichtig Publishing, 2017)
Background: Implants or implantable devices should integrate into the host tissue faster than fibrous capsule formation, in which the design of the interface is one of the biggest challenges. Generally, bioactive materials are not viable for load-bearing applications, so inert biomaterials are proposed. However, the surface must be modified through techniques such as coating with bioactive materials, roughness and sized pores. The aim of this research was to validate an approach for the evaluation of the tissue growth on implants of porous alumina coated with bioactive materials. Methods: Porous alumina implants were coated with 45S5 Bioglass (R) (BG) and hydroxyapatite (HA) and implanted in rat tibiae for a period of 28 days. Ex vivo resections were performed to analyze osseointegration, along with histological analysis, Scanning Electron Microscopy with Energy Dispersive X-Ray spectroscopy (SEM-EDX) line scanning, radiography and biomechanical testing. Results: Given that the process of implant integration needs with the bone tissue to be accelerated, it was then seen that BG acted to start the rapid integration, and HA acted to sustaining the process. Conclusions: Inert materials coated with bioglass and HA present a potential for application as bone substitutes, preferably with pores of diameters between 100 mu m and 400 mu m and, restrict for smaller than 100 mu m, because it prevents pores without organized tissue formation or vacant. Designed as functional gradient material, stand out for applications in bone tissue under load, where, being the porous surface responsible for the osseointegration and the inner material to bear and to transmit the loads.
Keywords: Bioactive glass; Coated surface; Hydroxyapatite; Osseointegration; Porous alumina implants